Characterization of Amperometric Laccase Biosensor Based on Carbon Nanotube. (2017) - Romero-Arcos, M.; Garnica-Romo, M.G.; Martínez-Flores, H.E.
Abstract: A highly sensitive and stable laccase biosensor has been developed based on multiwalled carbon nanotube (NTC). Scanning electron microscopy, X-ray diffraction, and Raman spectroscopy were applied for characterization of the surface morphology of the NTC. The properties of the biosensor NTC/LAC/GA were characterized by electrochemical impedance spectroscopy (EIS) and cyclic voltammetry (CV). The proposed biosensor exhibited excellent analytical performance such as a linear range between 0.5 μM to 150 μM, a detection limit of 0.50 μM, with a sensitivity of 2.81 μA L/μmol.